Understanding refugees' concepts of sexual and gender-based violence - Hough, C (Refugee Studies Centre, University of Oxford, 2013)
Sexual and gender-based violence prevention campaigns that incorporate culturally sensitive understanding will stand a better chance of breaking down barriers to accessing services.